STRATEGI PENGEMBANGAN USAHATANI KOPI ARABIKA (Coffea arabica) DI DESA PAGUR KECAMATAN PANYABUNGAN TIMUR KABUPATEN MANDAILING NATAL SUMATERA UTARA - Yuli Paisah; Fiddini Alham; Thursina Mahyuddin (Bajang Institute, 2024)
Mandailing Natal Regency is one of the coffee-producing areas in North Sumatra Province. The largest community coffee plantation in Mandailing Natal Regency belongs to Pagur Village, which is located in East Panyabungan District. This research was conducted with the aim of identifying and analyzing internal factors (strengths and weaknesses) and external factors (opportunities and threats) of arabica coffee farming in Pagur Village, Panyabungan Timur District and to analyze the right strategy to be implemented in developing coffee farming in Pagur Village. The survey method is the method chosen in carrying out this research. A total of 39 people from Pagur Village were chosen to be respondents or samples in the study. The analysis used in this study is descriptive analysis using SWOT analysis, Position Matrix and SWOT Matrix, to formulate